Stress Inducing Demands in Virtual Environments. (September 2018) - Finseth, Tor; Barnett, Neil; Shirtcliff, Elizabeth A.; Dorneich, Michael C.; Keren, Nir
This study investigated how simulated features in a virtual reality (VR) induce stress by means of user-focused demands in serious games. VR serious games have been used for therapeutic interventions, standardized stress tests, and occupational training. However, it is an open question how stress can be induced using serious games formal features, such as tasks/sensory modalities, music, pace of the game, and graphics. The Highrise VR standardized stress simulation was built to induce stress cohesively based on emotional, social, cognitive, and physical demands. The simulation induces stress by requiring coping with emotional demand (innate fear) of being at a simulated height, social demand of being evaluated by researchers, cognitive demand of a mental math task, and physical demand of balancing on a walking-plank. The stress response in participants was measured with two biomarkers: heart rate and salivary cortisol. Heart rate and salivary cortisol both showed significant and prolonged increases in response to the Highrise VR, suggesting that the task can successfully induce a stress response using game features. Among the participants, the response rate to the stressor was 77%, demonstrating a response rate on par with traditional standardized stress tests. Findings from this study warrant further investigation into how VR simulations induce stress for serious games and may add to a new body of literature that uses VR to investigate underlying mechanisms of physiological stress reactivity.